Pengaruh Peran Wali Kelas Dalam Kegiatan Belajar dari Rumah (BdR) Terhadap Keaktifan Peserta Didik Kelas XI MAN 1 Jombang - Rahmawati, Erma (Balai Diklat Keagamaan Surabaya, 2020)
The implementation of teaching and learning activities in madrasas since March 2020 has changed due tothe Covid-19 pandemic, the government has established the concept of BDR (Learning from Home) at alllevels of education. This study aims to determine the extent of the influence of the role of the homeroomteacher in BdR activities on the activeness of class XI students in MAN 1 Jombang. The method used in thisresearch is quantitative research methods. Data collection techniques that researchers use are observation,interviews, documentation, and questionnaires. For data analysis using the Durbin-Watson autocorrelationtest, and the Simultaneous F test. The results showed that there was an influence on the role of homeroomteacher on the activeness of class XI students in MAN 1 Jombang, amounting to 69.2 %.